One-year analysis of trends of COVID-19 in Libya: Cases, deaths, and laboratory testing - Elmehdawi, Rafik; Glessa, Sara; Elfakhri, Amal; Elhaddad, Ahmed; Elhassi, Ahmed (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Introduction: The coronavirus disease 2019 (COVID-19) epidemic in Libya started at the end of March 2020. Since then, the number of daily reported cases has progressively increased. Objectives: This study aims to analyze the trends and dynamics of the epidemic in Libya. Materials and Methods: The study analyzed the data reported daily by the Libyan national center of disease control. Results: The total number of tests performed per thousand people was 121.08 test/1000 people, which is a modest rate compared with countries categorized in the same income group. The overall positivity rate of all performed tests over 1 year was 18.1%. During most of the weeks, the positivity rate was far higher than the 5% rate indicating that the epidemic was out of control most of the year. The level of community transmission was moderate to substantial during most of the year, reflecting the weakness in applying the public health control measures. The calculated 1-year instant case-fatality rate of COVID-19 in Libya was 1.89%, comparable to that in other upper-middle-income countries. Conclusions: The number of performed tests in Libya during the 1st year of the COVID-19 epidemic is inadequate and must be at least doubled to increase the chances of diagnosing more potential cases. Based on the current positivity rate, the epidemic appears to be out of control since July 2021. This should urge the authorities to impose further enforcement of the standard public health measures.
Keywords: Community transmission; COVID-19; Libya; mortality; recovery